A comparative study on hydrogen storage properties of as-cast and extruded Mg-4.7Y-4.1Nd-0.5Zr alloys. (February 2022) - Chen, J.N.; Zhang, J.; He, J.H.; Zhou, X.J.; Lu, X.Z.; Chen, X.M.; Yu, L.P.; Zhou, D.W.
Abstract: In this paper, the as-cast and extruded Mg-4.7Y-4.1Nd-0.5Zr alloys were prepared, and their microstructures, hydrogen storage properties and catalytic mechanisms were systematically studied. The results show that the as-cast Mg-4.7Y-4.1Nd-0.5Zr alloy is mainly composed of Mg, Mg24 Y5 and Mg41 Nd5 phases, while the Mg41 Nd5 phase in the extruded alloy is dissolved into Mg matrix due to homogenization. After hydrogenation, the in - situ formed nano-particles of rare earth hydride REH x are uniformly distributed on the surface of MgH2, which exhibit remarkable catalytic effects on the subsequent hydrogenation and dehydrogenation of Mg matrix. According to the isothermal hydrogen absorption and desorption kinetic testing, the Mg-4.7Y-4.1Nd-0.5Zr alloys in the two states both exhibit good hydrogen sorption kinetics. Compared with pure Mg, the apparent activation energies of dehydrogenation reaction of the as-cast and extruded alloys are reduced to 114 kJ mol −1 H2 and 109 kJ mol −1 H2, respectively, which should be ascribed to the catalytic roles of YH2 and NdH2 nano-hydrides. Comparatively, the extruded alloy presents a more excellent dehydrogenation kinetics, and it can release more than 6 wt% of hydrogen within 15 min at 350 °C. First-principles calculations reveals that the rare earth hydrides YH2 and NdH2 improve the hydrogen storage performance of Mg alloy by weakening the bonding strength of the H–H bond within H2 molecule and the Mg–H bond within MgH2 . Highlights: The as-cast and extruded Mg-4.7Y-4.1Nd-0.5Zr alloys were prepared. The alloys in-situ form RE (Y/ Nd)H x ( x  = 2, 3) hydrides after hydrogenation. The RE (Y/Nd)H x ( x  = 2, 3) hydrides exhibit catalytic effects on Mg matrix. The dehydrogenation rate of extruded alloy is faster relative to as-cast alloy. The YH2 and NdH2 both weaken the bond strength of H–H within H2 and Mg–H with MgH2.